PERANAN PPAT DALAM PEMUNGUTAN BEA PEROLEHAN HAK TANAH DAN BANGUNAN (BPHTB) ON LINE ATAS TRANSAKSI JUAL BELI TANAH DAN BANGUNAN DI KOTA MAGELANG - Yunita Budi Chrissanni; Amin Purnawan (Jurnal Akta, 2017)
The research titled "The Role of Official Official Deed Officer (PPAT) in Collection of Land and Building Ownership Rights (BPHTB) Online on Land and Building Transaction in BPKAD Kota Magelang" to know how far the role of PPAT in PHTB collection and what obstacles and its solution in BPHTB collection on line in Magelang city.This research uses empirical juridical approach, in collecting data more emphasized on source of primary material, in the form of law and regulation, studying law norms and law science sera theory added by interview to the parties related to the problem in carefully.Based on the method, the research produces principally (1) the Land Actor (PPAT) as the Government Regulation Number 37 Year 1998 concerning PPAT Office Regulation and its implementation is stipulated in Regulation of the Minister of Agrarian Affairs / Head of National Land Agency Number 4 Year 1998 on Implementation of Government Regulation Number 3 In 1998, a general official as intended in Article 1868 of the Civil Code has the responsibility as a partner of the government in carrying out the BPHTB levy which in the Tax Payment of Land and Building Acquisition Rights (BPHTB) is regulated in Local Regulation of Magelang City No. 9 of 2010 on Customs Acquisition of Land and Building Rights (2) The obstacles that arise in the execution of Collection of Land Acquisition Rights of Land and Building (BPHTB) Online in Magelang city and what efforts are made to overcome obstacles is the tax value proposed by the taxpayer Not in accordance with INT (Land Value Index) y Which has been determined by BPKAD the solution regarding it is conducted survey of land and building location by BPHT object building by BPKAD, or taxpayer to clarify the value of BPHTB, if not found the solution to that matter then BPKAD use regulation of Mayor Magelang Regulation Number 7 of 2017 on Local Tax Service And Payment System On LineKeywords: BPHTB, On Line, PPAT